Analisis PERMA Nomor 1 Tahun 2016 tentang Mediasi terhadap Rendahnya Keberhasilan Mediasi di Pengadilan Agama Ponorogo - Melati, Aathiika Mutiara; Fawzi, Ramdan; Satria Hamdani, Fahmi Fatwa Rosyadi (Bandung Conference Series: Islamic Family Law, 2025)
Abstract. Civil cases in the Religious Courts, especially family disputes, often involve intense emotional conflicts between parties and therefore require effective resolution mechanisms. As an institution with the authority to handle these cases, the Ponorogo Religious Court is trying to implement mediation in accordance with Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. However, the success rate of mediation at the Ponorogo Religious Court is lower compared to other Religious Courts in the surrounding area. Therefore, this research raises the following problem: What are the factors that cause the low success of mediation in the Ponorogo Religious Court? and What is the analysis of PERMA Number 1 of 2016 regarding the low success factors of mediation in the Ponorogo Religious Court? This research uses qualitative methods with an empirical normative approach through data collection techniques in the form of in-depth interviews, literature studies and document analysis. The results of the research reveal that mediation has been carried out in accordance with the procedures in Supreme Court Regulation Number 1 of 2016 concerning Mediation in Court, however the mediation process is still less than optimal due to several factors, namely due to the strong determination of the parties, namely the plaintiff and defendant, the level of difficulty of the case, the lack of good faith from the parties in the presence of the parties, the less than optimal use of caucus and the limitations of the mediator in offering innovative solutions. So this led to the success of mediation at the Lower Ponorogo Religious Court Abstrak. Perkara perdata di lingkungan Pengadilan Agama, khususnya sengketa keluarga, seringkali melibatkan konflik emosional yang intens antar pihak sehingga memerlukan mekanisme penyelesaian yang efektif. Sebagai institusi yang berwenang menangani perkara tersebut, Pengadilan Agama Ponorogo berusaha mengimplementasikan mediasi sesuai Peraturan Mahkamah Agung Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan. Namun, tingkat keberhasilan mediasi di Pengadilan Agama Ponorogo lebih rendah dibandingkan dengan Pengadilan Agama lain di wilayah sekitarnya. Oleh karena itu, maka penelitian ini mengangkat permasalahan sebagai berikut: Apa saja faktor yang menyebabkan Rendahnya Keberhasilan Mediasi di Pengadilan Agama Ponorogo? dan Bagaimana Analisis PERMA Nomor 1 Tahun 2016 terhadap Faktor Rendahnya Keberhasilan Mediasi di Pengadilan Agama Ponorogo? Penelitian ini menggunakan metode kualitatif dengan pendekatan normatif empiris melalui teknik pengumpulan data berupa wawancara mendalam, studi literatur, dan analisis dokumen. Hasil penelitian mengungkapkan bahwa Mediasi telah dilaksanakan sesuai dengan prosedur dalam Peraturan Mahkamah Agung Nomor 1 Tahun 2016 tentang Mediasi di Pengadilan, namun berjalannya mediasi masih kurang optimal karena adanya beberapa faktor yakni disebabkan oleh tekad yang bulat dari para pihak yakni penggugat dan tergugat yang sudah kokoh, tingkat kesulitan kasus, kurangnya iktikad baik dari para pihak kehadiran para pihak, kurang optimalnya penggunaan kaukus dan keterbatasan mediator dalam menawarkan solusi yang inovatif. Sehingga hal tersebut menyebabkan keberhasilan mediasi di Pengadilan Agama Ponorogo Rendah